2016
DOI: 10.2106/jbjs.15.01028
|View full text |Cite
|
Sign up to set email alerts
|

Capital Femoral Growth Plate Extension Predicts Cam Morphology in a Longitudinal Radiographic Study

Abstract: Superior epiphyseal extension was directly and temporally associated with an increase in anteroposterior alpha angle and more cam-like morphology. This alteration in the capital femoral epiphysis occurred immediately before physeal closure (OBA stage 7/8). Given the association of epiphyseal extension with activities that increase shear forces across the physis, we proposed that epiphyseal extension may be an adaptive mechanism to stabilize the physis and prevent slipped capital femoral epiphysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 38 publications
2
34
0
1
Order By: Relevance
“… 10 A theoretical model suggested that recurrent mechanical impingement could lead to growth plate alterations and development of cam, 11 findings which have been reinforced by recent studies demonstrating that adolescents develop concurrent growth plate changes and cam morphology. 12 - 14 Although we have no kinematic data from our cadaveric subjects, this hypothesis is consistent with the increased incidence of cam morphology seen in the cohort with decreased pelvic incidence.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“… 10 A theoretical model suggested that recurrent mechanical impingement could lead to growth plate alterations and development of cam, 11 findings which have been reinforced by recent studies demonstrating that adolescents develop concurrent growth plate changes and cam morphology. 12 - 14 Although we have no kinematic data from our cadaveric subjects, this hypothesis is consistent with the increased incidence of cam morphology seen in the cohort with decreased pelvic incidence.…”
Section: Discussionsupporting
confidence: 71%
“… 11 Growth plate alterations have subsequently been identified prior to cam development in adolescents. 12 - 14 Relative anterior acetabular overcoverage (as a consequence of low pelvic incidence) would similarly increase the risk for repetitive mechanical impingement, and could subsequently lead to cam formation through this mechanism. A preliminary study supported this theory as it demonstrated that patients with bilateral cam morphology had lower PI than matched controls.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive epiphyseal extension into the metaphysis has been shown to be a precursor off Cam FAI morphology in adolescent athletes . However, it remains unclear whether the increased epiphyseal extension is a pathologic response of the proximal femoral epiphysis to the increased mechanical stress associated with vigorous sports or if it is an adaptive response that would protect the epiphysis from slip at the cost of leading to a Cam morphology as suggested by Morris et al In our study it was evident that the more mature hips depended upon the peripheral cupping for epiphyseal stability in comparison to the young hip in which the large tubercle was the area with higher stress concentration. The transition from a tubercle‐based model towards a peripheral cupping‐based model of epiphyseal stability demonstrated in our study confirms that during skeletal growth, increased repetitive forces to the capital femoral epiphysis lead to a higher concentration of stress in the periphery.…”
Section: Discussionsupporting
confidence: 51%
“…Those studies also indicated a concomitant peripheral growth of the epiphysis around the metaphysis, described as epiphyseal cupping. Increased epiphyseal cupping or extension of the epiphysis into the metaphysis has been described as a precursor of cam‐type morphology associated with femoroacetabular impingement (FAI) . Abnormal extension of the capital femoral epiphysis has been suggested as a pathological response to recurrent stress to the growth plate observed in adolescents involved in vigorous sports activities .…”
mentioning
confidence: 99%
“…Previous studies suggested that this transition in the mechanism that regulates epiphyseal stability may establish a mechanical environment susceptible for the development of SCFE or cam morphology. 15 , 19 – 21 Participation in vigorous sports activities may increase shear stress across the growth plate and has been associated with supraphysiologic epiphyseal extension into the anterosuperior metaphysis. 1 , 26 – 29 Although some authors have suggested that supraphysiologic epiphyseal extension is a pathologic response to increased recurring mechanical stress at the femoral head-neck junction, 1 , 24 , 26 , 29 others have proposed that excessive extension is an adaptive response to protect the growth plate from increased mechanical stress that could lead to SCFE.…”
Section: Discussionmentioning
confidence: 99%